2006
DOI: 10.5194/hessd-3-3727-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multimodel ensemble approach to assessment of climate change impacts on the hydrology and water resources of the Colorado River basin

Abstract: Abstract. Implications of 21st century climate change on the hydrology and water resources of the Colorado River basin were assessed using a multimodel ensemble approach in which downscaled and bias corrected output from 11 General Circulation Models (GCMs) was used to drive macroscale hydrology and water resources models. Downscaled climate scenarios (ensembles) were used as forcings to the Variable Infiltration Capacity (VIC) macroscale hydrology model, which in turn forced the Colorado River Reservoir Model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
195
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(213 citation statements)
references
References 22 publications
11
195
1
6
Order By: Relevance
“…Modelling studies in other parts of the world of climate change effects on the hydrology of mountain catchments and hydropower flows are somewhat limited, and findings are variable depending on the location and biophysical characteristics. Studies in North America have found considerable spatial variability in climate change impacts on hydrologic and hydropower systems in large basins, where in general hydropower will be adversely impacted under drier conditions as a result of decreases in flows, and under wetter conditions if inadequate storage exists to allow for seasonal hydrograph changes (Christensen et al, ; Christensen and Lettenmaier, ; Vicuna et al, , ; Minville et al, ; Cherry et al, ; Kerkhoven and Gan, ). Other studies have shown that there is considerable uncertainty among different climate models in simulating river flows and hydropower impacts over space (Markoff and Cullen, ; Kerkhoven and Gan, ), but that most models indicate large decreases in hydropower inflows and production because of greater competition for reservoir storage between hydropower and instream flow goals (Payne et al, ; Markoff and Cullen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling studies in other parts of the world of climate change effects on the hydrology of mountain catchments and hydropower flows are somewhat limited, and findings are variable depending on the location and biophysical characteristics. Studies in North America have found considerable spatial variability in climate change impacts on hydrologic and hydropower systems in large basins, where in general hydropower will be adversely impacted under drier conditions as a result of decreases in flows, and under wetter conditions if inadequate storage exists to allow for seasonal hydrograph changes (Christensen et al, ; Christensen and Lettenmaier, ; Vicuna et al, , ; Minville et al, ; Cherry et al, ; Kerkhoven and Gan, ). Other studies have shown that there is considerable uncertainty among different climate models in simulating river flows and hydropower impacts over space (Markoff and Cullen, ; Kerkhoven and Gan, ), but that most models indicate large decreases in hydropower inflows and production because of greater competition for reservoir storage between hydropower and instream flow goals (Payne et al, ; Markoff and Cullen, ).…”
Section: Discussionmentioning
confidence: 99%
“…If a lake is not spilling any water, the water is either filling the lake or used to generate electricity. A number of studies on climate change impacts on hydropower generation in other parts of the world have also found that the quantity and variability of annual unproductive spills will likely increase (Christensen et al, ; Christensen and Lettenmaier, ; Vicuna et al, , ; Minville et al, ; Cherry et al, ; Kerkhoven and Gan, ). Very few studies have indicated that flows and hydropower production would increase significantly in the longer term (Minville et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ajauro and New [2007] published a comprehensive review on the different ensemble forecast methods that are available and the overall combination approaches. Forecast ensembles have been used in climate change studies in the areas of climatology [ Stott and Forest , 2007], land use change [ Viney et al , 2009], and hydrology [e.g., Christensen and Lettenmaier , 2007; Bastola et al 2011]. Many hydrological studies have simulated ensembles based on different climate models or emission scenarios [ Horton et al , 2006; Jasper et al , 2004].…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…River basin-specific studies indicate that expected increases in future warming trends are expected to exacerbate these water resource impacts. For the Upper Colorado River Basin (UCRB), Christensen and Lettenmaier (2007) applied forecasted changes in temperature and precipitation from 11 climate models and report an 8-11% decrease in UCRB runoff by the end of the 21st century. Hoerling and Eischeid (2007), after examining 42 climate simulations for the UCRB, report likely average decreases in UCRB streamflow of 25% by 2030, and 45% by 2060.…”
Section: Study Motivationmentioning
confidence: 99%